2005
DOI: 10.1128/jvi.79.20.12999-13006.2005
|View full text |Cite
|
Sign up to set email alerts
|

Essential Elements of the Capsid Protein for Self-Assembly into Empty Virus-Like Particles of Hepatitis E Virus

Abstract: Hepatitis E virus (HEV) is a noncultivable virus that causes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
205
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(211 citation statements)
references
References 26 publications
2
205
1
1
Order By: Relevance
“…The 4 structural elements provide a flat interface that is largely hydrophobic in nature. Previous mutagenesis identified a cluster of 6 hydrophobic residues critical for dimeric interactions: A597, V598, A599, L601, and A602 (26). Another study found that the deletion of residues 585-610 led to reduced oligomerization and aberrant folding of the protein (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4 structural elements provide a flat interface that is largely hydrophobic in nature. Previous mutagenesis identified a cluster of 6 hydrophobic residues critical for dimeric interactions: A597, V598, A599, L601, and A602 (26). Another study found that the deletion of residues 585-610 led to reduced oligomerization and aberrant folding of the protein (27).…”
Section: Resultsmentioning
confidence: 99%
“…The P2 domain alone is capable of dimerization (26). Dimerization of the P2 domain is mediated by an extended loop (550-566) and 3 ␤-strands from the central ␤-barrel (␤18, ␤24, and ␤27).…”
Section: Resultsmentioning
confidence: 99%
“…The antigen used in the ELISA was HEV-like particles composed of a truncated open reading frame 2 (ORF2) protein of genotype I HEV expressed by a recombinant baculovirus in insect cells and was suspended with 0.5 M carbonate buffer (pH 12.5) at a concentration of 1 µg/ml [3]. The antigen solution (100 µl) was added to duplicate wells of 96-well microplates (Sumiron ELISA plate type H, Sumitomo Bakelite, Tokyo, Japan).…”
Section: Samplesmentioning
confidence: 99%
“…2 ,27 VLPs for Hepatitis E have been assembled using a truncated form of the virus capsid protein. 28 In immunization studies in mice these VLPs were able to induce systemic and mucosal immune responses following oral administration. 28,29 Furthermore, oral administration of the Hepatitis E VLPs to cynomologous monkeys induced IgM, IgA and IgG responses and was sufficient to protect against infection and disease on challenge with virus.…”
Section: Vlps Produced For Structurally Simple Non-enveloped Virusesmentioning
confidence: 99%
“…28 In immunization studies in mice these VLPs were able to induce systemic and mucosal immune responses following oral administration. 28,29 Furthermore, oral administration of the Hepatitis E VLPs to cynomologous monkeys induced IgM, IgA and IgG responses and was sufficient to protect against infection and disease on challenge with virus. 30 Thus there is clear potential for the application of these VLPs as a vaccine for hepatitis E.…”
Section: Vlps Produced For Structurally Simple Non-enveloped Virusesmentioning
confidence: 99%